The Effect of Attentional Bias on Emotions in Patients with Breast Cancer. - Han, Bingxue; Yan, Jialin; Liu, Jinxia; Xiong, Ruoyu; Teng, Shuai; Du, He; Liu, Chang; Fan, Huaju; Ji, Lili; Wang, Miaomiao; Jia, Liping; Lu, Guohua (International Journal of Behavioral Medicine, 2025)
Background: Attentional bias may influence the emotional experiences of breast cancer patients, both positively and negatively. This study aimed to investigate attentional bias in breast cancer patients and its impact on their emotions. Method: Thirty-eight breast cancer patients completed a modified dot-probe task and the Depression Anxiety and Stress Scale to assess attentional bias and emotional states. Attentional bias was measured by analyzing response times to different stimuli in the modified dot-probe task. Emotional stimuli included 80 pairs of facial images depicting sad-neutral, fearful-neutral, happy-neutral, and neutral–neutral expressions. Attentional bias components were observed at stimulus presentation durations of 300 ms and 1500 ms. Differences in emotional responses among breast cancer patients with varying attentional biases were compared. Results: Breast cancer patients exhibited attentional avoidance of sad and happy stimuli at 300 ms. Further analysis revealed that patients who exhibited attentional avoidance of sad stimuli at 300 ms reported higher levels of anxiety and stress. Those with attentional avoidance of fearful stimuli at 1500 ms reported increased anxiety, while individuals showing attentional avoidance of happy stimuli or difficulty disengaging from happy stimuli at 1500 ms reported higher levels of depression and stress. Conclusion: Breast cancer patients demonstrated an attentional bias toward emotional stimuli, particularly avoidance of sad and happy stimuli in 300 ms. Different components of attentional bias were associated with distinct negative emotional outcomes.